Эффект малых добавок углеродных нанотрубок на теплопроводность нанокомпозитов на основе сетчатого полицианурата - Корсканов, В.В.; Бардаш, Л.В.; Файнлейб, A.М. (Видавничий дім "Академперіодика" НАН України, 2009)
Дослiджено температурну та концентрацiйну залежностi теплопровiдностi композитiв на основi полiцiануратних сiток, якi наповненi вуглецевими нанотрубками (ВНТ). При масовiй концентрацiї ВНТ близько 0,03% виявлено стрибкоподiбне пiдвищення провiдностi тепла, що супроводжується рiзким зростанням температурного коефiцiєнта теплопровiдностi dλ/dT. The temperature and concentration dependence of the thermal conductivity of the composites based on a polycyanurate network filled with multi-walled carbon nanotubes (MWCNTs) are investigated. For the MWCNTs content of about 0.03 wt. %, the stick-slip increase of the thermal conduction accompanied with a sharp increase of the temperature coefficient of thermal conductivity dλ/dT has been found.